(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Quantification of tree biomass in the tropics is a time-consuming activity, especially the measurement of certain biomass components, such as the tree height, diameter at various part of the tree stem. This study assessed the Quantification of aboveground biomass and carbon sequestration potentials of Eucalyptus cameldulensis specie at Dayi Plantation, Katsina State, Nigeria. The plantation was stratified into three different age series (1989, 1990 and 1991). In each stratum, a non-destructive approach was adopted and (5) sample plots of 50 x 50m were laid across each of the three (3) age series. All standing trees were marked, numbered and their attribute such as diameter at breast height (DBH), diameter at three different position (bottom, middle and top) and height (HT) were measured and recorded. A constant value of wood density (0.58) was obtained from the web. A total number of 1,349 tree stands were recorded for the entire plantation and the total quantity of 25,295 kg/ha AGB was estimated for the plantation, the estimated carbon stock is 12,647.5 kg/ha and the sequestered carbon, which represents the amount of carbon dioxide absorbed and stored by the ecosystem over time is 46,374.17 kg/ha. Conclusively, it is believed that the result of this study serve as input to forest managers, researchers and policy makers in planning and management of Eucalyptus camaldulensis in the state or region with similar environmental conditions.